(untitled) (Universal International Scientific Journal, 2026)
The process of social protection of people should not be a temporary practice for one day, one week or one month, but a continuous process aimed at freeing them from the whirlpool of trials caused by life and living difficulties, and directing them to a bright future of prosperity and a decent lifestyle, like other representatives of society. From the very first days of his activity, our President gave a sufficiently well-founded understanding of how officials and state structures should communicate with the general public. In a short time, the process of dialogue between the people and the state has not only consisted of words, but has been bearing fruit and manifesting itself in the lives of every person in the country.